An exploratory study on workforce engagement of direct selling independent sales representatives. (30th April 2021) - Li, Yulong; Liao, Ying; Li, Jason
Based on data from Direct Selling Association's 2018 National Salesforce Survey, this study explores the conceptual structure of workforce engagement among direct selling independent sales representatives and its impact on work experience and job performance. Our statistical analyses revealed three conceptual dimensions of engagement among direct selling independent sales representatives, namely: emotional attachment with upline sponsors, meeting operational needs by the company and feeling belongingness to the company. We have also found that those who were millennials, perceived direct selling as a serious career path, and felt engaged would have better work experiences. In terms of job performances, highly engaged independent sales representatives appeared to hold more sales parties, but did not seem to achieve higher sales revenue or net profit per party.